The Palgrave Handbook of Contemporary Heritage Research
XXVI, 586 p.
Keywords: This book explores heritage from a wide range of perspectives and disciplines and in doing so provides a distinctive and deeply relevant survey of the field as it is currently researched, understood and practiced around the world.